2021
DOI: 10.1016/j.kint.2020.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Results from the IRoc-GN international registry of patients with COVID-19 and glomerular disease suggest close monitoring

Abstract: The effects of SARS-CoV-2 infection on individuals with immune-mediated glomerulonephritis, who are often undergoing immunosuppressive treatments, are unknown. Therefore, we created the International Registry of COVID infection in glomerulonephritis (IRoc-GN) and identified 40 patients with glomerulonephritis and COVID-19 followed in centers in North America and Europe. Detailed information on glomerulonephritis diagnosis, kidney parameters, and baseline immunosuppression prior to infection were recorded, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 39 publications
0
45
1
2
Order By: Relevance
“…Advanced CKD appears to be associated with an increased risk of severe infection, although causality remains unclear (57,58). Moreover, results from the International Registry of COVID infection in glomerulonephritis confirmed higher mortality (15% vs. 5%) and an increased risk of acute kidney injury (AKI) (39% vs. 14%) in this population compared with controls (59). Interestingly, however, immunosuppressive treatment before the onset of SARS-CoV2 infection was not associated with increased mortality or AKI in GD patients, not supporting the discontinuation of these medications.…”
Section: Immune-mediated Glomerular Diseasesmentioning
confidence: 80%
See 1 more Smart Citation
“…Advanced CKD appears to be associated with an increased risk of severe infection, although causality remains unclear (57,58). Moreover, results from the International Registry of COVID infection in glomerulonephritis confirmed higher mortality (15% vs. 5%) and an increased risk of acute kidney injury (AKI) (39% vs. 14%) in this population compared with controls (59). Interestingly, however, immunosuppressive treatment before the onset of SARS-CoV2 infection was not associated with increased mortality or AKI in GD patients, not supporting the discontinuation of these medications.…”
Section: Immune-mediated Glomerular Diseasesmentioning
confidence: 80%
“…Given the outcomes observed by Waldman et al (59), we should define the timing and priority of COVID-19 vaccination in patients with IMIDs associated with CKD, especially when pharmacologically immunosuppressed, considering how effective and safe the vaccine will be. Based on the available evidence, we believe that GD patients, more prone to develop severe clinical manifestations of SARS-CoV-19 infection, should undergo the COVID-19 vaccination because of a favorable risk/ benefit ratio.…”
Section: Immune-mediated Glomerular Diseasesmentioning
confidence: 99%
“…A paucity of data exists on the disease course of COVID-19 in patients on immunosuppression. An analysis of the International Registry of COVID infection in glomerulonephritis indicated that mortality rates are comparable to those observed in dialysis and transplant patients [ 15 ]. There are specific considerations in these patient groups, which have been recently outlined by the Immunonephrology Working Group of the European Renal Association - European Dialysis and Transplant Association (ERA-EDTA) [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The effects SARS-CoV-2 infection has on individuals with immune-mediated glomerulonephritis (GN) were studied by Waldman et al in the IRoc-GN international registry [90]. In this study, 40 patients with biopsy-proven GN and COVID-19 were compared to 80 controls without GN who were hospitalized with COVID-19.…”
Section: Covid-19 In Patients With Pre-existing Glomerulonephritismentioning
confidence: 99%